Die Mimikry des Völkerrechts Andrés Bellos - Keller-Kemmerer, Nina (Studien zur Geschichte des Völkerrechts, 2018)
"To this day, the history of international law is dominated by a Eurocentric historiography in which non-European worlds play a passive role at best. Master narratives of universalisation and progress may include their histories; however, they appear not in the form of actors, but as mere receivers. By analysing the first Hispano-American textbook on international law, this transdisciplinary study questions this narrative of passivity. In his compendium, published in 1833, the Chilean polymath Andrés Bello translated European doctrines of international law for use in the context of the "New World". Using a postcolonial approach, the study demonstrates that the imitation of the European discourse on international law was not a purely passive and submissive act, but deeply ambivalent behaviour which opens up a space for resistance and is reminiscent of Homi K. Bhabha's concept of mimicry."